Cryptosporidiosis in Yellow Nail Syndrome – A Rare Case Report - Kundu, Aditya; Srivastava, Saumya; Tak, Vibhor; Goyal, Jagdish P. (Infectious Disorders - Drug Targets, 2023)
Background: Cryptosporidium species infection causes malabsorption and severe diarrhea in immunocompromised hosts. Association of Yellow Nail Syndrome (YNS) and Cryptosporidiosis is rare and has not been reported till date. Immunity can also be affected in this case of YNS is associated with autoimmune disorders. Case Presentation: Here, we describe a case of persistent diarrhea in an 8 month old YNS patient. Modified Ziehl-Neelsen staining and Saffranine-Methylene blue revealed oocyts of Cryptosporidium species. Following appropriate treatment, the patient’s symptoms improved and the patient was discharged in a hemodynamically stable condition. Discussion: Cryptosporidiosis is a significant cause of morbidity and mortality in immunocompromised patients. YNS per se as well as treatment including steroids leads to immunosuppression in individuals making them susceptible host for opportunistic infections like Cryptosporidiosis. Conclusion: Clinicians should be aware of the condition and screen for Cryptosporidiosis in any immunocompromised patients with diarrheal symptoms, as parasitic infection like this are opportunistic in them.
Keywords: Modified Ziehl-Neelsen